Adjustable microstructure carbon molecular sieve membranes derived from thermally stable polyetherimide/polyimide blends for gas separation. (March 2017) - Fu, Ywu-Jang; Hu, Chien-Chieh; Lin, Di-Wei; Tsai, Hui-An; Huang, Shu-Hsien; Hung, Wei-Song; Lee, Kueir-Rarn; Lai, Juin-Yih
Abstract: Carbon molecular sieve (CMS) membranes were prepared by controlled pyrolysis of polyetherimide (PEI) blended with polyimide (PI). The microstructure and gas separation properties of the precursor membranes and supported CMS membranes were characterized in terms of the different weight ratios of PI to PEI. The thermogravimetric analysis indicated that the co-pyrolysis in the PEI/PI appeared above 450 °C. Both permeability and selectivity of supported CMS membranes increased with increasing PI content in the precursors. The positron annihilation lifetime (PAL) results showed that the free volume size and the pore size were enhanced as the PI content is increased and that there is a close relationship between the microstructures of polymer blend precursors and CMS membranes. These results confirmed that the microstructure and gas separation performance of CMS membranes can be adjusted by blending two thermally stable polymers. For CMS membrane derived from a precursor containing 75 wt% PI and pyrolyzed at 700 °C, the gas permeance for CO2 was 40 GPU and CO2 /N2 selectivity was 39. Graphical abstract: Highlights: CMS membranes derived from only thermally stable polymer blend precursor. The microstructure of CMS membranes significantly depend on the structure of polymer blends. Selectivity and permeability of CMS membranes increase with increasing polyimide content.